Evaluation of the effects of titanium dioxide nanoparticles on cultured Rana catesbeiana tailfin tissue - Hammond, S. Austin; Carew, Amanda; Helbing, Caren (Frontiers in Genetics, 2013)
Nanoparticles (NPs), materials that have one dimension less than 100 nm, are used in manufacturing, health, and food products, and consumer products including cosmetics, clothing, and household appliances. Their utility to industry is derived from their high surface-area-to-volume ratios and physico-chemical properties distinct from their bulk counterparts, but the near-certainty that NPs will be released into the environment raises the possibility that they could present health risks to humans and wildlife. The thyroid hormones (THs), thyroxine, and 3,3′,5-triiodothyronine (T3), are involved in development and metabolism in vertebrates including humans and frogs. Many of the processes of anuran metamorphosis are analogous to human post-embryonic development and disruption of TH action can have drastic effects. These shared features make the metamorphosis of anurans an excellent model for screening for endocrine disrupting chemicals (EDCs). We used the cultured tailfin (C-fin) assay to examine the exposure effects of 0.1–10 nM ( 8–800 ng/L) of three types of 20 nm TiO2 NPs (P25, M212, M262) and micron-sized TiO2 (μ TiO2) ±10 nM T3. The actual Ti levels were 40.9–64.7% of the nominal value. Real-time quantitative polymerase chain reaction (QPCR) was used to measure the relative amounts of mRNA transcripts encoding TH-responsive THs receptors (thra and thrb) and Rana larval keratin type I (rlk1), as well as the cellular stress-responsive heat shock protein 30 kDa (hsp30), superoxide dismutase (sod), and catalase (cat). The levels of the TH-responsive transcripts were largely unaffected by any form of TiO2. Some significant effects on stress-related transcripts were observed upon exposure to micron-sized TiO2, P25, and M212 while no effect was observed with M262 exposure. Therefore, the risk of adversely affecting amphibian tissue by disrupting TH-signaling or inducing cellular stress is low for these compounds relative to other previously-tested NPs.